2022
DOI: 10.3389/falgy.2022.898494
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Desensitization in Allergen Immunotherapy

Abstract: Allergen immunotherapy (AIT) is the only treatment with disease-transforming potential for allergic disorders. The immunological mechanisms associated with AIT can be divided along time in two phases: short-term, involving mast cell (MC) desensitization; and long-term, with a regulatory T cell (Treg) response with significant reduction of eosinophilia. This regulatory response is induced in about 70% of patients and lasts up to 3 years after AIT cessation. MC desensitization is characteristic of the initial ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…This is partly due to the lack of protocols describing MC desensitization and its readouts. Furthermore, current desensitization models largely use murine MCs and monoclonal IgE, while allergic patients present with a polyclonal IgE repertoire ( López-Sanz et al., 2022 ).…”
Section: Before You Beginmentioning
confidence: 99%
See 2 more Smart Citations
“…This is partly due to the lack of protocols describing MC desensitization and its readouts. Furthermore, current desensitization models largely use murine MCs and monoclonal IgE, while allergic patients present with a polyclonal IgE repertoire ( López-Sanz et al., 2022 ).…”
Section: Before You Beginmentioning
confidence: 99%
“…Desensitized MCs can be used directly for co-culture with other cell types, immunofluorescence, live imaging, and omics approaches. For complete details on the use and execution of this protocol, please refer to López-Sanz et al. (2022) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In AIT, the induction of allergen-specific IgG, IgG4, and IgA, which have IgE-blocking activity, has been well characterized [ 40 ], and their upregulation seems to be in line with clinical symptoms [ 41 ]. The main mechanism involves competitively inhibiting IgE for allergen binding, resulting in the reduction of IgE-induced FcεRI activation on mast cells, thus reducing degranulation and release of inflammatory mediators [ 42 ]. Additionally, binding of allergen-IgE complexes to low-affinity IgE receptors on B cells is inhibited, resulting in diminished IgE-facilitated presentation to T cells [ 40 ] ( Figure 4 ).…”
Section: Ig Responses Indicative Of Effective Aitmentioning
confidence: 99%
“…The GRASS trial revealed that SCIT or SLIT is associated with IgG- or IgA-blocking antibodies, respectively [ 15 ]. Humoral biomarkers could be measured both systemically or locally in serum and nasal fluids; and they could be useful to predict local responses characteristic of early AIT response [ 42 ].…”
Section: Ig Responses Indicative Of Effective Aitmentioning
confidence: 99%